A comparative study of the efficacy and functionality of 10 commercially available wrist-hand orthoses in healthy females during activities of daily living - Aranceta-Garza, Alejandra; Ross, Karyn (Frontiers in Rehabilitation Sciences, 2022)
Objective Optimal wrist/hand function facilitates the performance of activities of daily living (ADL), which are associated with independent living and increased quality of life. Rheumatological, musculoskeletal, neurological conditions or injuries can negatively impact hand/wrist function, with wrist-hand orthoses (WHOs) being prescribed to control motion and improve wrist alignment whilst enhancing hand/wrist functionality. The objective of this follow-up study was to quantify and assess the efficacy and functionality of ten commercially available WHOs during five ADLs. Design Randomised comparative functional study of the wrist/hand with and without WHOs. Participants Ten right-handed healthy female participants with no underlying condition nor pain affecting the wrist/hand which could influence their ability to undertake ADLs. Main outcome measures Primary outcome was ascertaining the impact of each WHO during five ADLs. Movement was quantified in sagittal, coronal, and transverse planes with and without WHO use. The resting position, maximum mean flexion, extension, pronation, supination, radial and ulnar deviation attained were quantified, with time spent in wrist flexion, wrist flexion(AND)ulnar deviation, wrist extension >15°, and radial deviation recorded. Finally, the time to complete each task was compared between conditions. Results At rest, four WHOs maintained the desired sagittal plane wrist position, with only one preventing radial deviation with variation observed in the transverse plane. All WHOs reduced mean maximum flexion, with only 10/50 tests (20%) showing successful restriction of flexion (p<0.05) with 14/50 (28%) showing a reduction of time spent in flexion (p<0.05). In 42/50 (84%), the wrist was extended >15° for a significant amount of time (p<0.05), with the wrist in radial deviation in 98% for a significant amount of time (p<0.001). The wrist was flexed and in ulnar deviation for a significant time for 6/50 (12%, p<0.05), while all WHOs impacted transverse movement with 27% reducing it significantly, and all tasks took longer to complete with 46% taking significantly longer (p<0.05). Conclusion WHOs did not control movement sufficiently to successfully manage any condition requiring motion restriction associated with pain relief and were found to increase the time to complete ADLs. Multifactorial design aspects influence functionality and there is a clear need for WHO redesign.